2018
DOI: 10.1152/ajpendo.00021.2018
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing identified specific circulating miRNA biomarkers for early detection of diabetes retinopathy

Abstract: Diabetic retinopathy (DR) is the leading cause of blindness in patients with diabetes. However, biomarkers for early detection of DR are still lacking. MicroRNAs (miRNAs) regulate multiple biological functions and are often deregulated in DR. We aimed to investigate whether circulating miRNAs can be used as biomarkers of early-stage DR. We used RNA-seq and qRT-PCR to identify differential serum miRNAs in patients with type 2 diabetes mellitus with DR (T2DM-DR), T2DM without DR (T2DM-no-DR), and healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…Such techniques should provide improved evaluation of retinal injury to both the neuronal unit as well as the microvasculature and allow for improved, earlier treatments, both local as well as systemic. Currently there are no systemic factors established for retinopathy risk screening outside of hyperglycemia (HgbA1c), glycemic variability, hypertension, and obstructive sleep apnea, although early reviews suggest some serum autoimmune inflammatory constituents (85) and circulating miRNA markers are associated with early stages of diabetic retinopathy (86), and certainly need to be further investigated for screening and to define chronologic progression.…”
Section: Implications For Diabetic Retinopathy Diagnostic Screening Amentioning
confidence: 99%
“…Such techniques should provide improved evaluation of retinal injury to both the neuronal unit as well as the microvasculature and allow for improved, earlier treatments, both local as well as systemic. Currently there are no systemic factors established for retinopathy risk screening outside of hyperglycemia (HgbA1c), glycemic variability, hypertension, and obstructive sleep apnea, although early reviews suggest some serum autoimmune inflammatory constituents (85) and circulating miRNA markers are associated with early stages of diabetic retinopathy (86), and certainly need to be further investigated for screening and to define chronologic progression.…”
Section: Implications For Diabetic Retinopathy Diagnostic Screening Amentioning
confidence: 99%
“…51 During the course of this study, other investigators attempted to identify dysregulated circulating miRNAs in DR in humans. [17][18][19][20][21][22][23] These studies were carried out in patients with type 1 diabetes, 17,18 type 2 diabetes [19][20][21][22] or diabetes type not reported, 23 using serum, 18,20,22,23 plasma 19,21 or endothelial progenitor cells cultured from isolated peripheral blood mononuclear cells. 17 They reported that angiogenic miRNAs are associated with incident DR, 18 as compared to subjects with idiopathic macular holes.…”
Section: Discussionmentioning
confidence: 99%
“…Given their high stability and omnipresence in body fluids, several studies have identified the potential of circulating miRNAs as biomarkers of diagnosis, prognosis and management of type 2 diabetes and its vascular complications . Despite this, the profile of circulating miRNAs in DR has been evaluated only recently …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of NF-κB signaling pathway significantly increases in diabetes rats, and the up-regulation of NF-κB p65 expression augments the generation of reactive oxygen species and further leads to the occurrence of microaneurysms, retinal neovascularization and vitreous hemorrhage, boosting the progression of retinopathy in diabetes rats [9][10][11]. Encoded by endogenous gene, microRNA (miRNA) is a non-coding single-stranded RNA molecule (containing about 21-23 nucleotides) and has the features of high conservation, time sequence and tissue specificity [12,13]. miRNAs can interact with the 3'UTR region of the mRNA for a specific target gene by sequence-specific mode to regulate the protein expression of target gene.…”
Section: Introductionmentioning
confidence: 99%